Pregnancy outcomes among women with type 1 diabetes mellitus using continuous subcutaneous insulin infusion versus multiple daily injections: A retrospective cohort study. (September 2019) - Dixon, Benjamin RS; Nankervis, Alison; Hopkins, Stephanie CN; Cade, Thomas J
Background: Insulin delivery options for pregnant women with type 1 diabetes mellitus are either continuous subcutaneous insulin infusion or multiple daily injections. The aim of this paper is to compare pregnancy outcomes in women with type 1 diabetes mellitus using continuous subcutaneous insulin infusion or multiple daily injections in pregnancy. Methods: Retrospective single-centre cohort study of 298 pregnancies booked between 2006 and 2016. Descriptive analysis was performed for HbA1c values. Logistic regression models were created to compare selected maternal and neonatal outcomes. Results: Continuous subcutaneous insulin infusion was associated with increased risk of large-for-gestational age (aOR 2.00, 95% CI 1.20–3.34) and preterm neonates (aOR 1.80, 95% CI 1.04–3.03). Continuous subcutaneous insulin infusion had no association with increased risk of adverse pregnancy outcomes. No difference in HbA1c values existed between groups. Conclusion: Using continuous subcutaneous insulin infusion for type 1 diabetes mellitus through pregnancy is associated with increased risk of large-for-gestational age and preterm neonates, without increased risk of associated adverse maternal or neonatal outcomes.